Możliwości i ograniczenia felietonu jako narzędzia kreowania wizerunku jego autora - Barańska-Szmitko, Anna (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2014)
The aim of this paper is to verify the capacities and limitations of the column (understood as a genre) as a tool for creating the image of its author. In the paper, the distinguishing features of a column are first presented, and then a hypothesis is proposed for predicting what attributes of its author might be generated by the column’s features. This hypothesis is juxtaposed against the results of empirical research. The main task of the study was to read the texts of one of two Polish columnists – Krzysztof Varga and Szymon Hołownia – and subsequently answer questions indicating the authors’ attributes. This procedure enabled an image of the text’s author to be recreated. The results showed the influence that the distinguishing features of a column have on the image of a text’s author for readers.